UPAYA MENINGKATKAN MOTIVASI BERWIRAUSAHA YANG BERBASIS ONLINE PADA MASYARAKAT DESA TANJAKAN - Aziz, Roikhan Mochamad; Haq, Dhiyaul; Meilani, Meilani; Zahroh, Sekar Aini (STKIP Andi Matappa, 2020)
The level of acceptance in Indonesia is quite large, many factors cause it, one of them less able to compete in the world of work. The purpose of this study is to introduce and motivate citizens about entrepreneurship by using technology that is being developed continuously. This research was conducted in Tanjakan Village, Rajeg District, Tangerang Regency, Banten. The method used is descriptive qualitative. The subject is the Tanjakan community itself. From this research, it can be seen that what is related to related citizens through online media, both, but minimation, understands how to do entrepreneurship using technology that makes citizens less courage to start a business.